Point-of-care diagnosis and risk factors of infantile, rotavirus-associated diarrhoea in Calabar, Nigeria - Samuel E. Nnukwu; Simon J. Utsalo; Olufunmilayo G. Oyero; Michel Ntemgwa; James A. Ayukekbong (AOSIS, 2017)
Background: Rotaviruses are the primary cause of acute gastroenteritis in young children worldwide and a significant proportion of these infections occur in Africa. Objectives: In the present study, we determined the prevalence and risk factors of rotavirus infection among children younger than age 5 years with or without diarrhoea in Calabar, Nigeria, using a rapid point-of-care test. Methods: Two hundred infants younger than age 5 years presenting with acute gastroenteritis and a control group of 200 infants without diarrhoea were tested for rotavirus. Each stool sample was homogenised in an extraction buffer and the supernatant added into the sample well of the Rida Quick rotavirus test cassette and allowed to run for 5 minutes at room temperature. When both the control band and test band were visible on the test cassette a positive result was recorded, whereas when only the control band was visible a negative results was recorded. Results: Rotavirus was detected in 25 (12.5%) of children with diarrhoea and in no children without diarrhoea. Our results demonstrated that children who were exclusively breast-fed by their mothers were not infected with rotavirus and that 92% of the infants infected with rotavirus experienced vomiting. Conclusion: These data demonstrate that asymptomatic rotavirus infection is rare and that rotavirus is commonly detected in stool samples of children suffering from diarrhoea with concomitant vomiting. Use of point-of-care rotavirus tests will enhance early diagnosis of rotavirus-associated diarrhoea and reduce irrational use of antibiotics.